Experimental investigation of CNC machining of elliptical pockets on AISI 304 stainless steel. (2016) - Patel, Divyangkumar Dharmendra; Dodiya, Hardikkumar Rasiklal; Lalwani, D.I.
The shape of a pocket geometry, a tool path strategy and various machining parameters (speed, feed rate, and depth of cut) affect pocket machining process in terms of machining time, surface finish, material removal rate, tool life, etc. Most of the literature related to pocket machining deals with the tool path generation and the effect of various machining parameters. But, the effect of the shape of a pocket geometry and the tool path strategy on the overall performance of pocket machining is scarcely reported. In the present work, an attempt has been made to investigate the effect of aspect ratio (i.e. changing the shape of pocket), feed rate and tool path strategies (zig-zag, spiral and contour parallel) on tool path length, cutting time, percentage utilisation of tool and average surface roughness in machining of elliptical pocket using design of experiments. A novel concept of percentage utilisation of a tool is developed to compare the different tool path strategies and different aspect ratios. The results show that tool path strategy and aspect ratio are significant factors that affect the tool path length and percentage utilisation of tool, whereas aspect ratio, feed rate and tool path strategy are important factors that affect cutting time and surface roughness.